Circular Economy Transformation in Textile and Batik Manufacturing: A Bibliometric and Systematic Review of Sustainable Industrial Practices - Fathan Mubina Dewadi; Muhamad Emir Purdiatama; Angga Setiawan; Iwan Ridwan (JADI (Jurnal Teknik Industri), 2026)
The textile and batik manufacturing industries generate significant environmental impacts due to intensive water consumption, chemical usage, and wastewater discharge during production processes. Circular Economy (CE) has emerged as a sustainable industrial approach emphasizing recycling, reuse, and resource efficiency to support green manufacturing transformation. This study aims to analyze the development of circular economy implementation in textile and batik manufacturing industries using bibliometric analysis and systematic literature review (SLR) approaches. Data were collected from Scopus, Web of Science, and Google Scholar databases covering publications from 2015–2026. Bibliometric analysis was conducted using VOSviewer to identify publication trends, thematic structures, and keyword relationships, while SLR was applied to synthesize findings related to sustainable manufacturing practices. The results indicate significant growth of CE-related publications after 2018, particularly in textile recycling, wastewater treatment, eco-friendly dyeing systems, and industrial sustainability. However, CE implementation in batik manufacturing remains limited due to financial, technological, and policy constraints. This study concludes that circular economy strategies possess strong potential for supporting sustainable industrial transformation and environmental sustainability in textile and batik manufacturing sectors.